Analysis of Accounting Knowledge, Perception, and Business Scale on the Use of Accounting Information Among MSMEs (UMKM) Actors in Cirebon City - Akmal As'Ad; Muhamad Najmi; Rizal Saputra; Roni Mulyatno (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study analyzes the effect of accounting knowledge, perceptions, and business scale on the use of accounting information in MSMEs in Cirebon City. Using quantitative methods with multiple linear regression, data were collected from 97 MSME respondents with annual revenue of at least Rp 50 million. Data collection was conducted during February-March. The results showed that accounting knowledge has a significant effect on the use of accounting information, while perception and business scale do not have a significant effect individually. However, the overall model is valid, indicating that all variables collectively have an impact on the use of accounting data. The findings support the importance of improving accounting literacy among MSMEs to improve financial decision-making.